Комплексные единицы слообразовазовательной системы в их взаимодействии - Евсеева, Ирина (Studia Rossica Posnaniensia, 2015)
Word-building types and word-building nests are hierarchy-arranged system formations. These complex units fully reflect both the activity of derivatives and the continuity of a given semantic field. A semantic field is formed by means of semantic derivational links that constitute the derivational system.